KESIAPAN SEKOLAH DALAM PELAKSANAAN PROGRAM GURU PENGGERAK DI SMAN 1 KEC. SULIKI KAB. LIMA PULUH KOTA - Arminingtyas, Mutiara; Rahmanelli, Rahmanelli (JURNAL BUANA, 2023)
This research was conducted aiming to 1)knowing how the level of teacher readiness in implementing the Program Guru Penggerak at SMAN 1 Kec. Suliki Kab. Lima Puluh Kota, and 2)knowing how the school is prepared in implementing the Program Guru Penggerak at SMAN 1 Kec. Suliki. This research is a type of combination research (mix method) that uses quantitative research and qualitative research. The research method used is exploratory sequential, where the researcher conducts qualitative research at first to get an overview and explore the views of the research sample so that the right instrument can be identified to be used in quantitative research. With a sample of 30 respondets, the researcher will distribute questionnaires to then be processed using the percentage data test. The results of this study found that the level of school readiness in implementing the Progam Guru Penggerak was in the very ready category with an average percentage value of 90% which consisted of the readiness of teachers in implementing the Program Guru Penggerak in the very ready category with an average percentage value of 93,68%, and the readiness of school in implementing the Program Guru Penggerak is categorized as very ready with an average percentage value of 85,66%.